2017
DOI: 10.1038/s41598-017-08420-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel approach to determination of sorption in pervaporation process: a case study of isopropanol dehydration by polyamidoimideurea membranes

Abstract: Development of novel membranes with optimal performance, selectivity, and stability is a key research area in membrane technology. In the present work aromatic polyamidoimideurea (PAIU) is synthesized and tested as promising membrane material for separation of water and alcohol mixtures. The PAIU membrane structure, density, and transport properties are studied. Mass transfer of water and isopropanol through the membrane is estimated by sorption and pervaporation tests to determine equilibrium sorption degree,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…However, the experience showed that such membranes contain residual amounts of NMP solvent. In order to eliminate the influence of residual solvent (NMP) on membrane properties, the obtained membranes were subjected to the special treatment with methanol that displaces NMP and washes it out 23 . Membranes were immersed into methanol, left to stand for three days, then thoroughly washed with methanol, and dried at 40 о С in vacuum for two weeks 4042 .…”
Section: Methodsmentioning
confidence: 99%
“…However, the experience showed that such membranes contain residual amounts of NMP solvent. In order to eliminate the influence of residual solvent (NMP) on membrane properties, the obtained membranes were subjected to the special treatment with methanol that displaces NMP and washes it out 23 . Membranes were immersed into methanol, left to stand for three days, then thoroughly washed with methanol, and dried at 40 о С in vacuum for two weeks 4042 .…”
Section: Methodsmentioning
confidence: 99%
“…Thus, water molecules can be easily sorbed into the membrane matrix. [49] 3.9 | Pervaporation study 3.9.1 | Effect of azeotropic mixtures and wt% of DBP on PV Figure 11 demonstrates the effect of different wt% of DBP content on the total permeation flux and separation factor for the developed membranes at 30 C in dehydrating water/isopropanol and water/1,4-dioxane mixtures at their azeotropic point. It is observed that the permeation flux was increased from DBP-1 to DBP-4 owing to the increased plasticizing content, as discussed in the swelling study, and this is expected due to extensive hydrogenbonding interactions between the carbonyl oxygen and ester oxygen of DBP and OH group of NaAlg.…”
Section: Swelling Studymentioning
confidence: 99%
“…The transport of binary liquid mixtures through a nonporous polymeric membrane in the PV process is typically described by a solution-diffusion mechanism. [49] The rate of permeation and separation factor is determined by the solubility and diffusivity of each component of the feed to be separated. In the separation process, the diffusion step controls the transport of penetrants by establishing a fast equilibrium distribution between the bulk feed and the upstream surface of a membrane.…”
Section: Diffusion Coefficientsmentioning
confidence: 99%
“…In spite of the various, complex methods for determining the diffusion coefficient, the researchers usually do not evaluate the value of diffusion coefficient but only estimate parameters that describe the effectiveness of investigated membranes (e.g., PSI , flux and separation factor) [ 17 , 18 , 23 , 24 , 25 , 26 ]. Much less frequently sorption and diffusion coefficients are considered [ 8 , 27 , 28 , 29 ], which requires additional experimental setups. Such approach is in contrast to what we can find in the analysis of permeation of gases where determination of D is crucial.…”
Section: Introductionmentioning
confidence: 99%